A new species of Trigastrotheca Cameron (Hymenoptera: Braconidae: Braconinae) from Thailand - Raweearamwong, Marisa; Quicke, Donald L. J.; Butcher, Buntika A. (Zootaxa, 2020)
A new species of Trigastrotheca Cameron, 1906 from Doi Phu Kha National Park, Nan province, Thailand is described and illustrated based on a female specimen collected by light trapping, bringing the total number of Trigastrotheca species known from Thailand to three; T. doiphukhaensis Raweearamwong, Quicke & Butcher, sp. nov., T. pariyanonthae Quicke & Butcher, 2017, and T. sureeratae Quicke & Butcher, 2017. The new species differs markedly in coloration from other Thai species and is most similar to T. tridentata (Enderlein) from which it is differentiated. A checklist to the 14 species known of Trigastrotheca with their distributions is provided.